2020
DOI: 10.1186/s12905-020-01090-7
|View full text |Cite
|
Sign up to set email alerts
|

“The whole package deal”: experiences of overweight/obese women living with polycystic ovary syndrome

Abstract: Background Polycystic Ovary Syndrome (PCOS) is a common female reproductive disorder with multiple manifestations. There are relatively few qualitative studies exploring the nature of living with PCOS despite its high prevalence. Qualitative research can enhance clinical practice via the provision of patient insights into the experience of living with their condition. Methods We conducted two focus groups and three semi-structured in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…Another strength of this study was the involvement of peri- and post-menopausal women whose experiences and beliefs may not be transferable from the experiences of women of reproductive age. Previous qualitative studies largely involved women under 50 years of age [ 30 , 31 , 41 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another strength of this study was the involvement of peri- and post-menopausal women whose experiences and beliefs may not be transferable from the experiences of women of reproductive age. Previous qualitative studies largely involved women under 50 years of age [ 30 , 31 , 41 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous qualitative studies have also showed that women have a need for social support and connection with other women with PCOS [ 27 , 48 50 ] and support groups often enable women to do just that, whether that be online or locally [ 27 , 29 , 33 , 51 , 52 ]. A study evaluating the effectiveness of a nurse-led support group left participants feeling more empowered in self-management and benefitting from informational exchanges [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Coffey et al, those with PCOS experienced poorer health related quality of life compared to those associated with other chronic conditions such as asthma, epilepsy and coronary heart disease (32). Ee et al found that acne and facial hair were major contributors to poor mental health in some women (27). Himelein and Thatcher reported body dysmorphia was very high in nulliparous women with PCOS (33).…”
Section: Mental Healthmentioning
confidence: 99%